One Year Outcomes of an International Multicentre Prospective Cohort Study on the Gore Excluder Iliac Branch Endoprosthesis for Aorto-Iliac Aneurysms. (August 2021) - van der Veen, Daphne; Holewijn, Suzanne; Bellosta, Raffaello; van Sterkenburg, Steven M.M.; Heyligers, Jan M.M.; Ficarelli, Ilaria; Gómez Palonés, Francisco J.; Mangialardi, Nicola; Mosquera, Nilo J.; Holden, Andrew; Reijnen, Michel M.P.J.; ,; et al.
Abstract : Objective: The Gore Excluder Iliac Branch Endoprosthesis (IBE) was developed to preserve perfusion in the hypogastric artery after endovascular repair of aorto-iliac aneurysms. This study reports the 12 month technical and clinical outcomes of treatment with this device. Methods: This study was a physician initiated international multicentre, prospective cohort study. The primary endpoint was primary patency of the hypogastric branch at 12 months. Secondary endpoints included technical and clinical outcomes. Patients with an indication for elective treatment with the Gore Excluder IBE were enrolled between March 2015 and August 2018. Baseline and procedural characteristics, imaging data, physical examinations and questionnaire data (Walking Impairment Questionnaire [WIQ], EuroQol-5-Dimensions [EQ5D], International Index of Erectile Function 5 [IIEF-5]) were collected through 12 month follow up. Results: One hundred patients were enrolled of which 97% were male, with a median age of 70.0 years (interquartile range [IQR] 64.5 – 75.5 years). An abdominal aortic aneurysm (AAA) above threshold for treatment was found in 42.7% and in the remaining patients the iliac artery diameter was the indication for treatment. The maximum common iliac artery (CIA) diameter on the Gore Excluder IBE treated side was 35.5 mm (IQR 30.8 – 42.0) mm. Twenty-two patients received a bilateral and seven patients had an isolated IBE. Median procedural time was 151 minutes (IQR 117 – 193 minutes) with a median hospital stay of four days (IQR 3 – 5 days). Primary patency of the IBE at 12 month follow up was 91.3%. Primary patency for patients treated inside and outside the instructions for use were 91.8% and 85.7%, respectively ( p  = .059). Freedom from secondary interventions was 98% and 97% at 30 days and 12 months, respectively. CIA and AAA diameters decreased significantly through 12 months. IIEF-5 and EQ5D scores remained stable through follow up. Patency of the contralateral internal iliac artery led to better IIEF-5 outcomes. WIQ scores decreased at 30 days and returned to baseline values through 12 months. Conclusion: Use of the Gore Excluder IBE for the treatment of aorto-iliac aneurysms shows a satisfactory primary patency through 12 months, with significant decrease of diameters, a low re-intervention rate, and favourable clinical outcomes.